Pure in body, pure in mind? A sociohistorical perspective on the marketisation of pure foods in great Britain. (April 2020) - Alex O'Hagan, Lauren
Highlights: Food companies use purity as a rhetorical device to sell their products. Purity is played up by food companies for the ultimate goal of profit. They give physical, mental, spiritual and environmental connotations to purity. A sociohistorical approach to social semiotics ensures archival-grounded analyses. It uncovers sociocultural meanings, historical rules and institutional powers. Abstract: This paper explores the marketisation of 'pure' from the late nineteenth century to modern-day using examples of food packaging and advertising. Adopting a sociohistorical approach to the theoretical perspective of social semiotics, it draws attention to the arbitrariness of the term and demonstrates how, over time, advertisers have constructed a particular discourse that equates the purity of a food product with a physical, mental or spiritual type of purity. In doing so, they invest food with a moral authority and legitimacy that leads consumers to understand commodities through marketing discourses and buy into the lifestyle and cultural value that the product promises, although it may not be true. In emphasising how purity has historically been used as a rhetorical device to sell products, the study hopes to encourage consumers to challenge food advertising and be aware of the myths that it can create in order to become empowered and make informed choices about supposedly healthy products.